Quaternion Kahler flat manifolds - Dotti, Isabel Graciela (2001)
It is the main purpose of this lecture to indicate a rather general method to construct quaternion-Kahler compact flat manifolds. This construction will give many families of quaternion Kahler manifolds of dimensions 8 or greater, which admit no Kahler structure  (see Section 3). This will follow from the  explicit calculation of the Betti numbers of the manifolds involved.